PENYULUHAN TENTANG IMPROVING STUDENTS' LISTENING SKILL MELALUI STORYTELLING APPLICATION DI SMK NEGERI 5 SAMARINDA - Abdul Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2022)
Learning that uses technology in the form of learning applications that are used as a means for teachers and students to facilitate the learning process that aims to achieve the success of learning and also create an effective learning atmosphere, learning by using mobile learning media can make students exciting and fun. The researcher took one of the learning application technologies that could be useful for students to achieve English language learning, especially in listening, which was the storytelling application. This application can be downloaded via Google Play Store and used by students to explain or describe listening skills in English. This application provides various interesting stories with English vocabulary and pronunciation that Indonesian students easily understand